Trabalho digno e decente na era das plataformas digitais: um estudo do trabalho em aplicativos de serviços. - Silva, Rita de Cássia Tavares da (2024)
Today's societies are undergoing profound transformations due to a new complex and multifaceted reality. These changes are driven mainly by technological evolution, which is becoming increasingly evident in our days. The computerization of production, digital work, carried out remotely or through platforms and applications, and the constant search for technical and digital improvement are becoming predominant aspects of human relations, providing greater agility in several areas of life, including leisure, daily life and work. The current technological advances have been considerably changing labor relations. With the introduction of new technologies and the change in the centrality of work, in addition to the development of new devices and software, there is a growing proximity between the worker (who provides the service or offers the product) and the customer. It is in this context that the provision of services through applications, or "apps", as they are popularly known, comes into play. These applications, originating from projects initially developed by startups, are spreading widely throughout societies. The current rise of work provides accessible employment opportunities to a wide range of people, including those who face barriers to traditional employment. Many app-based companies have become responsible for providing a source of income, work, or temporary activities, causing a real change in the traditional concept of work and employment. However, many workers deal with precarious working conditions, insufficient pay, lack of benefits, and lack of social protection. It is observed that the algorithmic nature of platforms can lead to discriminatory labor management practices, raising ethical questions about the power exercised by companies. In addition to the implications for workers, work via apps also has broader repercussions on the economy and society, generating fierce competition between workers on these platforms. Therefore, this dissertation proposes an analysis of how new forms of work intermediated by digital applications, especially services, impact the dignity of workers, examining the role of digital platforms in shaping the future of work and in adapting labor laws and regulations. It aims to highlight the importance of fundamental principles and decent work, examining the relationship between decent work and the preservation of the human dignity of workers, as defined by the International Labor Organization (ILO) as a basis for the application of labor standards. In addition, it aims to present how other countries are positioning themselves and what are the directives recommended by the European Union (EU) on work on digital platforms. The dissertation is structured in four chapters, addressing everything from the evolution of work in platform capitalism to proposed laws that deal with the use of Official Intelligence in Brazil, as well as the “Self-Employed Platform Worker”, whose study is a bibliographic and deductive research that uses various resources to promote a comprehensive analysis on the subject.